(untitled) (Journal of Atomic and Molecular Sciences, 2016)
We theoretically investigated high-order harmonic generation and isolated attosecond pulse generation from a model of helium atom by two methods: numerically solve time dependent Schrödinger equation (TDSE) by splitting-operator method and Lewenstein's strong field approximation theory. A left circularly polarized pulse (800 nm) is combined to a right circular polarized pulse (1200 nm) with a time delay of 4 fs. A supercontinuum spectrum plateau with a broad bandwidth of 215 eV (from 230 to 445 eV) is obtained for the case of I_0=7×1014W/cm². By superposing a bandwidth of 70 eV in the plateau region, an linear polarized isolated attosecond pulse with the duration of about 56 as can be obtained. Moreover, we illustrate the quantum path control in terms of the time-frequency analysis by Morlet wavelet transform method.